Problematika Implementasi Kurikulum Merdeka di SDN 114/II Rantau Pandan: Studi Kasus Guru Kelas - Ismarina Rosida; Dilla Desfrita Wahyuni; Syofiani; Rieke Alyusfitri (STKIP Subang, 2026)
This study aims to describe the challenges of implementing the Independent Curriculum in elementary schools from the perspective of classroom teachers. The study used a qualitative approach with a case study conducted at SDN 114/II Rantau Pandan. The subjects were classroom teachers directly involved in the implementation of the Independent Curriculum. Data were collected through in-depth interviews, learning observations, and documentation studies, then analyzed using an interactive analysis model. The results showed that the implementation of the Independent Curriculum has not been optimal. Classroom teachers still face obstacles such as limited conceptual understanding, difficulties in developing teaching modules, suboptimal implementation of differentiated learning, and obstacles in implementing assessments. Administrative burdens and minimal ongoing mentoring also affect curriculum implementation. This study concludes that systemic support is needed to improve the quality of the implementation of the Independent Curriculum in elementary schools